Estrategia didáctica "Aprendo Actuando" y su influencia en el aprendizaje de competencias de los niños y niñas de cinco años en el área Lógico - Matemática de la Institución Educativa Inicial Nº 293, Sagrado Corazón de Jesús, del caserío Los Olivos del distrito de Nueva Cajamarca - Cabanillas Albites, Maritza (2008)
Logical - Mathematical it is an area to develop and to show the sharpness of the mind, therefore the development of capacities and mathematical knowledge is useful, as much for the daily life as for the learning of other necessary disciplines for the personal development of the boy. To teach Logical - Mathematical he is problematic important and a present one in all the countries. The impact of the Technologies of the information and the communications (TIC) on education in general and individual on the Mathematical one, together with the necessity of the use of this science for the development of the logical thought, the capacity of reasoning and the dynamic and changing understanding of the objective reality, force more and more to perfect quickly the methods and procedures of the education of the Mathematical one, so that a high capacity of adaptability and ability obtains the formation of a withdrawn gift to learn to learn. In the Educativa tnstitution of the Level of lnitial education Nº the 293 of the small village Olive trees of the Nueva district Cajamarca, the difficulties in the learning that appears in the logical area of - mathematical, are accentuated, this entails to a preoccupation generalized on the part of the educational ones, in the measurement that makes withdraw young of this level with deficiencies that are going to repel in the level of primary Education. Reason by which, the made investigation has had as objective to determine the influence of the Didactic Strategy "I learn Acting" in the learning of competitions of the children and children of five years in the mathematical logical area of the Educative lnstitution lnitial Nº 293, Asylum Heart of Jesus, the small village the Olive trees, the Nueva district Cajamarca, in 2006. The theory of the cooperative learning, of the active character of the student in the process education learning, of the social character of the learning, of the historicismo and of the character mediatizado of the human psyche, they have allowed hipotetizar that the didactic strategy "I Learn Acting" logician will influence significantly in the learning competition(competence) of the children and five-year-old girls in the area - mathematics of the Educational lnitial lnstitution N º 293, Sacred Heart of Jesus, of the hamlet The Olive trees, of the district of New Cajamarca, in the year 2006; The same one that has been confirmed(resisted) by the supposition that the didactic strategy "I Learn Acting" logician will not influence significantly in the learning competition(competence) of the children and five-year-old girls in the area - mathematics of the Educational lnitial lnstitution N° 293, Sacred Heart of Jesus, of the hamlet The Olive trees, of the district of New Cajamarca, in the year 2006. The study sample was constituted by 25 children and children to those who the didactic strategy was administered to them to a test written before and after the development of learning sessions applying I learn acting, according to the design of preexperimental investigation of pretest - posttest with a single group. The statistical processing of the comparison of averages of matched up measurements, by means of the determination of t - Student, being tc= 29.28 > tt = 1.711, has allowed to verify the hypothesis, concluding that the didactic strategy "I learn Acting" to significantly influenced in the learning of competitions of the children and children of five years in the Mathematical Logical area of the Educativa lnstitution lnitial Nº 293, Asylum Heart of Jesus, the small village the Olive trees, the Nueva district Cajamarca, in 2006.